Carbon dioxide adsorption of diallylamine-modified natural rubber with modified silica particles - D. Tumnantong; K. Panploo; B. Chalermsinsuwan; P. Prasassarakich; S. Poompradub (eXPRESS Polymer Letters)
In this study, modified natural rubber (MNR) was used as a solid adsorbent for carbon dioxide (CO2) capture. The chemical structure of the NR latex was modified by diallylamine. Moreover, the silica particles were modified by (3-aminopropyl)trimethoxysilane, N-[(3-trimethoxysilyl)propyl]ethylenediamine, or N-[(3-trimethoxysilyl)propyl]diethylenetriamine (mono-, di- and tri-amines) to improve the CO2 capture ability of the MNR. The CO2 adsorption capacity of the MNR foam composite was increased 3- to 5-fold after filling with unmodified or modified silica particles. The mechanism for CO2 adsorption of the MNR composite was a combination of physisorption and chemisorption. At 100 °C, the highest CO2 adsorption capacity of MNR foam composite (10.35 mg/g of adsorbent) was obtained by adding tri-amine-modified silica particles. Finally, the MNR foam composite material could be regenerated process for more than 20 CO2 adsorption cycles.